Introduced hybrid ash : Fraxinus excelsior x F. angustifolia in Ireland and its potential for interbreeding with native ash - Thomasset, Muriel (Trinity College (Dublin, Ireland). Department of Botany, 2011)
Fraxinus excelsior L. is the only native ash in Ireland. It has important economic value for timber exploitation. After the introduction of grants by Irish government in the 1990s for planting native broadleaf trees, with an extra premium of hardwood species including ash, provenances of supposed F. excelsior were imported from continental Europe to fulfil the needs of foresters and farmers. At the time of planting, the trees appeared to be of excellent quality but after some years, the trees started to show very bad stem form, poor vigour and growth, and unusual morphology. Management authorities, farmers and foresters have questioned the authenticity and origin of the imported trees. Indeed very pale and brown buds observed on introduced trees are more characteristic of another species F. angustifolia Vahl present in continental Europe, with usually a more southern distribution than F. excelsior. Moreover, natural hybrids between these two species have been observed in two different zones where the species grow in sympatry. Reciprocal artificial crosses have also been made.
Keywords: Botany, Ph.D.; Ph.D. Trinity College Dublin